On your marks, get set, pause: what care home teams should consider before partnering with a trial research group. (2nd January 2023) - Spilsbury, Karen; Peryer, Guy; Devi, Reena; Haunch, Kirsty; Jordao, Magda; Thompson, Carl; Goodman, Claire
Abstract : Research has the potential to inform and enhance the care and experiences of people living and working in care homes. While there is a growing interest in research relevant for care homes, there is also a need to ensure that staff, residents and their families and friends are supported when considering taking part in research; particularly in a type of research called a 'trial'. Trials are a type of research study that can help guide decisions about the best treatment, care and support for both residents (and their families and friends) and care home staff. While potentially important, trials are demanding for both care homes and trial research teams. Before agreeing to support a trial, there are questions a care home manager, staff, residents and their families and friends can consider. These questions are outlined in this article, and the answers to these will help a care home to determine whether they have the capacity, readiness and relationships to support a trial. By taking the time to 'pause' and ask 'are we ready?', care teams can support both care and science.